2001
DOI: 10.1080/713671772
|View full text |Cite
|
Sign up to set email alerts
|

The association between nutrition knowledge and eating behavior in male and female adolescents in the US

Abstract: Some factors that could influence adolescent eating behavior include: peer influences, nutrition knowledge and beliefs, mass media, and parental dietary habits. The purpose of this study was to examine the correlation of nutrition knowledge and eating behavior of a sample of middle school children. The participants were 532 students in the sixth, seventh, and eighth grades between the ages of 11 and 13 from Shawnee Middle School in Lima, Ohio. The students were asked to answer a questionnaire, CANKAP (Comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 11 publications
3
15
0
2
Order By: Relevance
“…This finding has been confirmed by other studies in both adolescents (1,(21)(22)(23)25,(33)(34)(35) and adults (27,28,30,(36)(37)(38) . In subgroups under 12 years of age, however, gender was less predictive (21,22,33) .…”
Section: Level Of Nutritional Knowledgesupporting
confidence: 86%
See 1 more Smart Citation
“…This finding has been confirmed by other studies in both adolescents (1,(21)(22)(23)25,(33)(34)(35) and adults (27,28,30,(36)(37)(38) . In subgroups under 12 years of age, however, gender was less predictive (21,22,33) .…”
Section: Level Of Nutritional Knowledgesupporting
confidence: 86%
“…A level of approximately 60 % of questions answered correctly, as in the HELENA study, was also found in smaller samples of adolescents in single European countries (20,21) and abroad (1,22) , whereas mostly lower scores (of around 40 %) were found in US adolescents (22)(23)(24)(25) . Interestingly, adults do not seem to have any better nutritional knowledge compared with adolescents, not even college students (26)(27)(28)(29) , although in a recent Australian study 72 % of questions were answered correctly (30) .…”
Section: Level Of Nutritional Knowledgesupporting
confidence: 55%
“…Girls are more likely to report healthier food choices, more fruits and vegetables and less high-fat content foods, such as potato crisps and chips, hamburgers, cakes, and pastries (Andersen et al, 1995;Inchley et al, 2001;Paulus et al, 2001). This may be attributed to the increased nutrition knowledge observed in women (Pirouznia, 2001), but most likely to the weight concerns of young females and their involvement in slimming diets, which make them more willing to choose low-fat foods such as fruits and vegetables. However, girls are also known to have lower intakes of essential nutrients and minerals, especially iron and calcium (Rolland-Cachera et al, 2000;Lytle et al, 2002;Suitor and Cleason, 2002), since they consume fewer servings of meat, dairy, and cereal products.…”
Section: Discussionmentioning
confidence: 99%
“…38 In US students, eating behaviour correlated with nutritional knowledge in seventh and eighth but not in sixth grade students. 39 Increasing age and type of school was found to correlate significantly with nutritional knowledge but not with the degree of overweight. 40 In addition, in the pilot study, in general, girls had higher knowledge scores than boys, and there was a tendency for higher scores with increasing age and lower scores with increasing BMI in girls only.…”
Section: Dietary Qualitymentioning
confidence: 91%